Cell biology: More than skin deep - Fuchs, Elaine (J Cell Biol, 2015)
In studying how stem cells make and maintain tissues, nearly every chapter of a cell biology textbook is of interest. The field even allows us to venture where no chapters have yet been written. In studying this basic problem, we are continually bombarded by nature’s surprises and challenges.